1999
DOI: 10.1007/bf02433292
|View full text |Cite
|
Sign up to set email alerts
|

Regulation ofin vitro human lymphocyte blast transformation associated with γ-globulin fraction containing a carbohydrate component

Abstract: Carbohydrate-enriched components were isolated from human serum y-globulin by chelation of associated transition metals. Similar to the initial y-globulin preparation, these components stimulate in vitro blast transformation of human lymphocytes from healthy donors and inhibit subsequent phytomitogen-induced lymphocyte blast transformation. Key words: y-globulin; carbohydrate component, lymphocyte blast transformationThe ability of y-globulin to maintain a definite level of human lymphocyte blast transformatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 12 publications
2
10
0
Order By: Relevance
“…Our findings and previously reported data [4] indicate that LBT and NCT observed in vitro in the presence of human y-globulin [5,6] are due to the release of carbohydrate-rich components inhibiting NK cells and stimulating lymphocyte proliferation, This process results from intra-and intermolecular cross-linking in y-globulin molecule, which improves protein stability in diluted water solutions. Comparative analysis using 4x10 -2 4x10 -3 4x10 -~ a special algorithm showed that the effective dose of carbohydrate-rich components (0.1 lag/ml) inhibiting in vitro cytotoxic functions of human mononuclear cells ( Fig.…”
Section: Resultssupporting
confidence: 51%
See 4 more Smart Citations
“…Our findings and previously reported data [4] indicate that LBT and NCT observed in vitro in the presence of human y-globulin [5,6] are due to the release of carbohydrate-rich components inhibiting NK cells and stimulating lymphocyte proliferation, This process results from intra-and intermolecular cross-linking in y-globulin molecule, which improves protein stability in diluted water solutions. Comparative analysis using 4x10 -2 4x10 -3 4x10 -~ a special algorithm showed that the effective dose of carbohydrate-rich components (0.1 lag/ml) inhibiting in vitro cytotoxic functions of human mononuclear cells ( Fig.…”
Section: Resultssupporting
confidence: 51%
“…Comparative analysis using 4x10 -2 4x10 -3 4x10 -~ a special algorithm showed that the effective dose of carbohydrate-rich components (0.1 lag/ml) inhibiting in vitro cytotoxic functions of human mononuclear cells ( Fig. 1) corresponded to concentrations of 60 ng/ ml carbohydrate component and 70 ng/ml y-globulin stimulating lymphocyte proliferation [4]. Therefore, the revealed effects are mediated by y-globulin-associated fractions released during the action of chelating agents not only under rigorous [1,4], but also under neutral conditions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations